Current Status of HIV/AIDS in South Asia - Rodrigo, C.; Rajapakse, S. (My University, 2009)
BACKGROUND: According to the United Nations Joint Program on HIV/AIDS, 33.2 million adults and children are living with the infection worldwide. Of these, two to three million are estimated to be in South Asia. All countries of the region have a low prevalence of human immunodeficiency virus (HIV). However, it is important to review the current epidemiological data to identify the trends of infection as it would have implications on prevention. MATERIALS AND METHODS: We performed a MEDLINE search using phrases 'South Asia' plus 'HIV', 'AIDS', and names of individual countries in South Asia (limits: articles published in last 10 years, in English language). Clinical trials, reviews, meta-analyses, letters, editorials, and practice guidelines were all considered. The following countries were included as belonging to South Asia; Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan and Sri Lanka. Recent estimates and data on country status, and details of national control programs were obtained from websites of international agencies such as the World Bank and United Nations Joint Program on HIV/AIDS (UNAIDS). RESULTS AND DISCUSSION: This review looks into many aspects of HIV infection in South Asia including country profiles with regard to infection, economic and psychological burden of illness and treatment issues in the South Asian context.